SALIENT ELEMENTS OF DEMOTIVATION FACTORS FROM ESL LEARNERS’ PERSPECTIVES - Fairil Hasbullah; Rafizah Mohd Rawian; Nurul Imtiaz Abd Gani; Noor Hashima Abd. Aziz (Journal of Islamic, Social, Economics and Development, 2023)
The study of demotivation, or the adverse aspects of motivation, is a topic that warrants more attention, particularly due to its direct impact on the educational experiences of English as a Second Language (ESL) learners at the tertiary level within Malaysian Higher Education Institutions (MHEIs). The aim of this research was to examine the factors that demotivate ESL learners who are presently enrolled in an English proficiency course at MHEI. The data were collected from a sample of twenty individuals using semi-structured interviews. Based on the coding and thematic analysis conducted, this study has revealed four prominent characteristics that contribute to demotivation factors from ESL learners’ perspectives. These elements include: (1) the presence of language barrier, (2) lack of self-confidence, (3) limited vocabulary in the English language, and (4) issues of resentment and dejection. By gaining a deeper knowledge of these aspects, educators and policy makers may enhance the ESL learning process, hence fostering increased motivation among ESL learners to acquire proficiency in the English language.